2022
DOI: 10.18517/ijaseit.12.2.12493
|View full text |Cite
|
Sign up to set email alerts
|

Stock Performance and Fishers’ Perception of Grouper and Snapper Fisheries in the Saleh Bay, Indonesia

Abstract: The legal basis of managing grouper and snapper fisheries in Saleh Bay is the Governor Regulation of West Nusa Tenggara No. 32 of 2018. This study aims to assess stock performance and understand fishers' perception of the regulation. In this study, we used length-based assessment, perception analysis, and Rapid Appraisal for Fisheries technique. The overall results showed that the implementation of the governor fisheries management regulation was still not optimal, although the potential spawning ratio (SPR) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Although catch compositions in coral reef fisheries are often diverse and include fishes from most trophic and functional roles (Humphries et al 2019), fishers in Indonesia typically target large carnivorous fishes as they are highly valued in export markets (Khasanah et al 2020). For example, the export of snappers (Lutjanidae) and groupers (Serranidae) is a lucrative industry in Indonesia that yields approximately 56 million dollars annually and has resulted in overexploitation for many of these species (Efendi et al 2020). Thus, export markets incentivize exploitation of carnivores and can lead to more dramatic impacts on carnivores than herbivores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although catch compositions in coral reef fisheries are often diverse and include fishes from most trophic and functional roles (Humphries et al 2019), fishers in Indonesia typically target large carnivorous fishes as they are highly valued in export markets (Khasanah et al 2020). For example, the export of snappers (Lutjanidae) and groupers (Serranidae) is a lucrative industry in Indonesia that yields approximately 56 million dollars annually and has resulted in overexploitation for many of these species (Efendi et al 2020). Thus, export markets incentivize exploitation of carnivores and can lead to more dramatic impacts on carnivores than herbivores.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that fishing will be the dominant driver of size spectra slopes when all species are aggregated because fishers typically target large‐bodied individuals as was the case for reef fishes in Fiji and US‐affiliated Pacific islands (Wilson et al 2010, Robinson et al 2017). Also, we predict that fishing will have a greater impact on size spectra slopes of carnivores than herbivores due to the high value and desirability of large‐bodied piscivores in Indonesian export markets (Efendi et al 2020). Although previous studies found that empirically estimated size spectra slopes (all species aggregated) were insensitive to habitat conditions (Nash et al 2016, Robinson et al 2017), food web models suggest that structural complexity and benthic resources can affect the size distribution of carnivores and herbivores (Rogers et al 2014, Rogers et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the presence of coral reefs, the diversity of grouper caught, based on each fishing gear, showed that the diversity belongs to the moderate category and the seagrasses and coral reefs in the surrounding waters seems to be in good conditions in Saleh Bay, which is necessary to maintain its sustainability in future as well. The problems with over-exploitation of grouper and the use of destructive fishing gear must be considered to be solved to prevent the degradation of the grouper population and their habitats [34]. Supervision and monitoring that have been carried out by governmental and nongovernmental organizations, as well as local communities ("POKMASWAS") [35] [36] need to be supported by all stakeholders in order to improve fisheries management in Saleh Bay.…”
Section: Variola Albimarginatamentioning
confidence: 99%
“…One measure that can be applied to address the tendency of fishermen to catch small groupers, thereby preventing them from reaching maturity and reproducing, is to regulate the minimum legal size (MLS) that fishermen are allowed to catch [9,[16][17][18]. Minimum legal size policies for groupers are especially important when there are signs of recruitment overfishing and/or growth overfishing [18][19][20][21], such as those observed in Kwandang Bay.…”
Section: Introductionmentioning
confidence: 99%